Summary of baseline household survey results: Rupandehi, Nepal - Center for Environmental and Agricultural Policy Research, Extension and Development (2013)
This report, prepared by Nepal's Center for Environmental and Agricultural Policy Research, Extension and Development (CEAPRED), provides a summary of the main results of a household baseline survey carried out in early 2011in 7 villages, with 137 households, in the Rupandehi CCAFS site in Nepal. The survey was carried out using the standardized CCAFS household baseline tool.